Engenharia de cristais aplicada nos fármacos nitroimidazólicos: secnidazol e benznidazol - Bezerra, Beatriz Pinheiro (2017)
Secnidazole and benznidazole drugs are key nitroimidazoles for the treatment of diseases affecting economically disadvantaged populations. In this work we address two problems, the first of the secnidazol, a widely used drug, lacking studies on the possible phase transformations that is possible, since it is a hydrate, in which form it is marketed.The second target of study is benznidazole, the drug of choice for the treatment of Chagas Disease and of low solubility and considerable toxicity, for which thereare no records of cocrystalsin the literature. We used the methods of crystal engineering with the purpose of knowing the behavior of the crystalline structure of secnidazol and formulating cocrystalsof benznidazole. Both were crystallized using techniques such as: slow evaporation, slurry,mechanochemical activation in a wide range of solubilization conditions and temperature. All material produced was characterized by thermal, spectroscopic and structural techniques. For secnidazole two polymorphs of anhydrous and benznidazole, a new solidform with oxalic acid, a cocrystal hydrated with phenol, three isomorphic solvates with salicylic acid and three polymorphs of the cocrystal with the same coformer were identified and characterized. Cocrystalswith salicylic acid showed satisfactory stability and better solubilitycompared to pure drug. In summary, we observed that the commercial form of secnidazole, although stable, should be the subject of careful quality control of anhydrous polymorphs. In addition, we verified that it is possible to optimize the physico-chemical properties of benznidazole with the advent of cocrystallization. We conclude, therefore, that the engineering of crystals when applied to pharmaceutical solids can facilitate the understanding and add value of them by controlling their physicochemical properties.